Senior management's consensus on quality improvement decision processes implications on quality performance of selected Philippine manufacturing firms - Quero, Rachel A.; Supangco, Vivien T. (Quezon City College of Business Administration, University of the Philippines Diliman, 2005)
Consensus, or the level of agreement among the senior management team of a firm, had been the subject of interest in strategic management literature. Prior studies generally seemed to suggest that a higher level of agreement among the executive team, composed of the CEO and the heads of the functional units, would be associated with enhanced firm performance. The Uncertainty Reduction Theory explains that agreement among members on organization roles and processes would improve the predictability of their behaviors. Moreover, the reduction of stress associated with ambiguity would enable members to concentrate more fully on the tasks at hand or to the substance of their decisions,thereby improving management and enhancing firm performance. This study extended prior research on consensus by finding out if senior managers'consensus on quality improvement decision processes (i.e. management procedures for selecting an improvement theme or project for the firm, and for implementing the chosen improvement theme or project) will be positively related to firm quality performance. In addition, this study attempted to find out if the firm's emphasis on differentiation strategy vis-a-vis cost leadership strategy will moderate the relationship between consensus on quality improvement and firm quality performance. Furthermore, this study also determined if perceptions on market uncertainty will moderate the relationship between consensus on quality improvement and firm quality performance. Furthermore, this study also determined if perceptions on market uncertainty will moderate the relationship between consensus on quality improvement and the quality performance of firms. A sample of 45 firms was selected from the food processing industry and the automotive parts manufacturing industry in the Philippines. An average of fours senior managers served as respondents from each firm. The respondents were mostly composed of the CEO and the heads of the functional units pertaining to production, marketing, finance, and human resource management. In each firm, the degree of consensus or level of agreement on quality improvement among the executive team was measured using the standard deviation of their responses to a multiple-item questionnaire...
Vita.
Thesis (Doctor of Philosophy in Business Administration)--University of the Philippines Diliman
Keywords: Manufacturing industries -- Management. -- Philippines; Manufacturing industries -- Quality control. -- Philippines; Total quality management -- Philippines